2014
DOI: 10.1021/je400835u
|View full text |Cite
|
Sign up to set email alerts
|

Excess Molar Volumes and Viscosities of Binary Systems of Butylcyclohexane with n-Alkanes (C7 to C14) at T = 293.15 K to 313.15 K

Abstract: Experimental values of densities and viscosities have been measured in the binary mixtures of butylcyclohexane (BCH) with n-heptane, n-octane, n-nonane, n-decane, n-dodecane, and ntetradecane at temperatures T = (293.15 to 313.15) K and pressure p = 0.1 MPa over the entire mole fraction range. The excess molar volumes (V m E ) and viscosity deviations (Δη) are calculated, and then the changes of V m E and Δη with the composition of BCH are fitted to the Redlich−Kister equation. The values of densities increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(115 citation statements)
references
References 22 publications
11
104
0
Order By: Relevance
“…U c (ρ) = 0.69 kg·m –3 for T < 343.15 K and U c (ρ) = 2.0 kg·m –3 for T ≥ 343.15 K; n -butylbenzene, U c (ρ) = 0.17 kg·m –3 for T < 343.15 K and b Reference : Equation for best of density of n -hexadecane is ρ/kg·m 3 = 956.848 – [0.557634 × T /K] + [2.68578 × 10 –4 × ( T /K) 2 ] – [1.24436 × 10 –7 × ( T /K) 3 ]. c Reference . d Reference . e Reference . f Reference . g Reference . h Reference . i Reference . j Reference . Equation for best of density of butylcyclohexane is ρ/kg·m 3 = 1127.02 – [1.46341 × T /K] + [1.17912 × 10 –3 × ( T /K) 2 ]. k Reference . l Reference . m Reference . n Reference . Equation for best of density of toluene is ρ/kg·m 3 = 1.18621 × 10 3 – [1.47573 × T /K] + 2.08566 × 10 –3 × ( T /K) 2 – 2.61945 × 10 –6 ( T /K) 3 . o Reference . p Reference . q Reference . r Reference . s Reference . t Reference . u Reference . v Reference . w References and for error. x Reference . y Reference . z Reference . …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…U c (ρ) = 0.69 kg·m –3 for T < 343.15 K and U c (ρ) = 2.0 kg·m –3 for T ≥ 343.15 K; n -butylbenzene, U c (ρ) = 0.17 kg·m –3 for T < 343.15 K and b Reference : Equation for best of density of n -hexadecane is ρ/kg·m 3 = 956.848 – [0.557634 × T /K] + [2.68578 × 10 –4 × ( T /K) 2 ] – [1.24436 × 10 –7 × ( T /K) 3 ]. c Reference . d Reference . e Reference . f Reference . g Reference . h Reference . i Reference . j Reference . Equation for best of density of butylcyclohexane is ρ/kg·m 3 = 1127.02 – [1.46341 × T /K] + [1.17912 × 10 –3 × ( T /K) 2 ]. k Reference . l Reference . m Reference . n Reference . Equation for best of density of toluene is ρ/kg·m 3 = 1.18621 × 10 3 – [1.47573 × T /K] + 2.08566 × 10 –3 × ( T /K) 2 – 2.61945 × 10 –6 ( T /K) 3 . o Reference . p Reference . q Reference . r Reference . s Reference . t Reference . u Reference . v Reference . w References and for error. x Reference . y Reference . z Reference . …”
Section: Resultsmentioning
confidence: 99%
“… a Reference . b Reference . c Reference . d Reference . e Reference . f Reference . g Reference . h Reference . i Reference . j Reference . k Reference . l Reference . m Reference . n Reference . o Reference . p Reference . q Reference . r Reference . s Reference . t Reference . u Reference . v Reference . w Reference . x Reference . y Reference . z Literature values for viscosity of hexylbenzene were converted from mm 2 ·s –1 in ref using density values in the current work. aa Reference . ab Standard uncertainties u are u ( T ) = 0.01 K, expanded uncertainties U c are U c (η) = 0.01 mPa·s. The average pressure P for these measurements was 0.102 MPa with an expanded uncertainty U c ( P ) = 0.002 MPa (level of confidence = 0.95, k = 2). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dooley et al have demonstrated that cyclic compounds need to be present in surrogate mixtures to produce combustion behavior that is similar to jet fuel . Surrogate mixtures have included cyclohexanes with substituents up to four carbons long. The properties of binary mixtures of n -butylcyclohexane in various linear alkanes (C 6 to C 16 ) , have been reported, but no study has published the properties of dodecane and hexadecane in t -butylcyclohexane and isobutylcyclohexane, which are isomers of n -butylcyclohexane. Isobutylcyclohexane has been found in the jet propellant, Endothermic Hydrocarbon Fuel-Tianjin University (EHF-TU), and is also formed during the catalytic cracking of heavier fuel compounds .…”
Section: Introductionmentioning
confidence: 99%